The Role of IGF-1 for Fracture Risk in Men - Vandenput, Liesbeth; Sjögren, Klara; Svensson, Johan; Ohlsson, Claes (Frontiers in Endocrinology, 2012)
Growth hormone and insulin-like growth factor-1 (IGF-1) are essential for the achievement of normal longitudinal bone growth and bone mass. Preclinical studies using various knockout models have shown that both endocrine (mostly liver-derived) IGF-1 and bone-derived IGF-1 contribute to normal longitudinal skeletal growth and cortical bone size. Since bone size is an important determinant of bone strength, and hence fracture risk, we evaluated the predictive role of serum IGF-1 for fracture risk. The population-based Osteoporotic Fractures in Men Sweden cohort recently showed for the first time that older men with low serum IGF-1 levels have an increased fracture risk, especially for the two most important fracture types, hip and vertebral fractures. This association between serum IGF-1 and incident fracture risk is partly mediated via bone mineral density. Future studies are required to identify the mechanisms by which endocrine and local IGF-1 regulate skeletal growth and bone size. In addition, possible mediators affecting the impact of IGF-1 on fractures in men remain to be elucidated.